2014
DOI: 10.2478/aucft-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Probiotic Strains from Human Milk in Breastfed Infants with Respiratory Infections

Abstract: Isolation and industrial exploitation of probiotics from human milk is a goal for worldwide milk biotechnology centres because of their modulation effect on the immune system in infants and adults. In the proposed study we have analysed fermentation patterns of Lactobacilli isolated from human milk, the reliability of API 50 CH carbohydrate fermentation system and a possible link between lactose concentrations and fermentation profiles on carbohydrates. We had succesfully identified three species of Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Previous studies have demonstrated that SeNPs can be synthesized by bacteria ( Sasidharan and Balakrishnaraja, 2014 ); however, the main disadvantage was the production of large-sized SeNPs ( Hnain et al, 2013 ). In the present study, SeNPs size particles ranged between 3 and 50 nm in diameter which was not in agreement with the other study ( Hnain et al, 2013 ), which reported a size range of SeNPs between 100 and 550 nm, with a mean size of 245 nm ( Neamtu et al, 2014 ). Similarly, L. acidophilus and Bifidobacterium sp.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Previous studies have demonstrated that SeNPs can be synthesized by bacteria ( Sasidharan and Balakrishnaraja, 2014 ); however, the main disadvantage was the production of large-sized SeNPs ( Hnain et al, 2013 ). In the present study, SeNPs size particles ranged between 3 and 50 nm in diameter which was not in agreement with the other study ( Hnain et al, 2013 ), which reported a size range of SeNPs between 100 and 550 nm, with a mean size of 245 nm ( Neamtu et al, 2014 ). Similarly, L. acidophilus and Bifidobacterium sp.…”
Section: Discussioncontrasting
confidence: 95%
“…In the present study, the LAB isolate HM1 from human breast milk was found to be similar to L. paracasei . Neamtu et al (2014) reported that seven LAB isolates obtained from human breast milk were identified as L. paracasei subsp . paracasei according to their ability to ferment 19 different sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Plates were incubated at 37°C for 24 -48 h (Carr et al, 2002). The Gram-staining and biochemical tests (catalase test, Kliger's iron test, sugar fermentation test, and casein digestion test) were performed for further identification (Smibert and Krieg, 1994;Neamtu et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Liquid medicinal substances (in the form of emulsion), solids (in suspension form), hydrophilic or hydrophobic medicinal substances and living cells may be encapsulated in microparticles by the coacervation technology, provided that the active substances are insoluble or very poorly soluble in the polymeric matrix/coating and are compatible with the polymer used in microencapsulation [ 53 ]. According to the factor causing the desolvation, the polymeric systems involved in the reaction and the phase separation mechanisms, coacervation can be of two kinds: simple coacervation, which generally occurs in the presence of a single polymer through the dehydration mechanism caused by the addition of an electrolyte/salt/desolvating liquid to the reaction medium, or complex coacervation, which occurs in the presence of two or more incompatible polymers by an electrostatic reaction [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Physico-chemical Properties Of Sodium Alginatementioning
confidence: 99%